CD4+ T helper 2 cell–macrophage crosstalk induces IL-24–mediated breast cancer suppression - Bo Wang; Yun Xia; Can Zhou; Yuhan Zeng; Heehwa G. Son; Shadmehr Demehri (JCI Insight, 2025)
CD4+ T cells contribute to antitumor immunity and are implicated in the efficacy of cancer immunotherapies. In particular, CD4+ T helper 2 (Th2) cells were recently found to block spontaneous breast carcinogenesis. However, the antitumor potential of Th2 cells in targeting established breast cancer remains uncertain. Herein, we demonstrate that Th2 cells induced by the topical calcipotriol/thymic stromal lymphopoietin cytokine axis suppressed the growth of established mammary tumors in mice. Interleukin-24 (IL-24), an anticancer cytokine, was highly upregulated in macrophages infiltrating calcipotriol-treated mammary tumors. Macrophages expressed IL-24 in response to IL-4 signaling in combination with Toll-like receptor 4 (TLR4) agonists (e.g., HMGB1) in vitro. Calcipotriol treatment significantly increased HMGB1 release by tumor cells in vivo. CD4+ T cell depletion reduced HMGB1 and IL-24 expression, reversing calcipotriol’s therapeutic efficacy. Macrophage depletion and TLR4 inhibition also reduced the therapeutic efficacy of calcipotriol. Importantly, calcipotriol treatment failed to control mammary tumors lacking the IL-24 receptor on tumor cells. Collectively, our findings reveal that Th2 cell–macrophage crosstalk leads to IL-24–mediated tumor cell death, highlighting a promising therapeutic strategy to tackle breast cancer.